Uncovering self-management needs to better design for people living with lymphoedema. Issue 2 (3rd July 2019) - Kopanoglu, Teksin; Beverley, Katie; Eggbeer, Dominic; Walters, Andrew
Abstract: This paper reports on the application of design-based tools used to uncover the needs of people living with a chronic condition. It was built on increasing rhetoric calling for greater involvement of patients in the creation of appropriate support mechanisms and presents a means to achieve this using design approaches and tools. The paper presents the development and use of scenario-based design probes to facilitate the participation of People Living with Lymphoedema (PLWL) early in the design process. Lymphoedema is a chronic condition requiring a cumbersome everyday management routine. Self-management is necessary to increase quality of life and decrease complications and hospitalisation. However, consistent practice of self-management among PLWL is low and the need to improve support is recognised. This research explored how PLWL's transitions towards becoming experts of their condition might be supported. Literature describing the lymphoedema experience was systematically investigated from a behavioural perspective to develop scenario-based probes. These probes provided rich insights by facilitating the envisioning of alternative futures to self-management support with interview participants with lymphoedema. To inform the design of better support for chronic conditions, the stages and components of behaviour change for lymphoedema self-management and the associated support needs are presented.